Analisis Cluster Hierarki Metode Single Linkage Pada Kabupaten/Kota di Provinsi Sumatera Barat Berdasarkan Indikator Kesehatan - Diah Rahmahadi Thamrin; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2022)
Health indicators are variables that are needed to estimate the conditions and changes faced by an area in the health sector. Health indicators are needed by the government to plan development in the health sector inaorderitoaachieve optimal resultsiin accordance with the conditions of each region. This study aims to group districts/cities in West Sumatra Provinceabasedion health indicators in 2020 and interpret the characteristics of each cluster that has been formed by using a single linkage method of hierarchical cluster analysis. The results of the grouping are dividedainto five clusters, the first cluster consists of the Mentawai Islands Regency. The second cluster consists of 12 regencies/cities namely Pesisir Selatan Regency, Padang Pariaman Regency, West Pasaman Regency, Agam Regency, Pasaman Regency, Dharmasraya Regency, South Solok Regency, Sawahlunto City, Bukittinggi City, Payakumbuh City, Solok City and Padang Panjang City. The third cluster consists of 4 regencies, namely Solok Regency, Tanah Datar Regency, Fifty Kota Regency and Sijunjung Regency. The fourth cluster consists of Kota Pariaman. The fifth cluster consists of the City of Padang.